Study the interaction of amino acids, sugars, thermal treatment and cooking technique on the formation of acrylamide in potato models - Bachir, Nivine; Haddarah, Amira; Sepulcre, Franscesc; Pujola, Montserrat (Food chemistry, 2023)
•Only Asn-GFS, Sucrose, and Glu-Fru synthetic potato models contained acrylamide.•Glutamine-based models didn’t not contain acrylamide after thermal treatment.•Sodium alginate might have an inhibitory effect on acrylamide formation.•Deep frying showed a strong association between oil uptake and acrylamide formation. This study unveiled the effect of the suspected precursors of acrylamide (asparagine, glutamine) combined/separated with different formulations of glucose, fructose, and sucrose. To better understand the interaction between acrylamide precursors, cooking technique (deep vs air frying), and temperature (170 °C vs 190 °C), seven potato models from starch, sugars, amino acids, water and hydrocolloids (alginate and agar) were formulated. In line with previous findings, the present results showed that asparagine, glucose and fructose played an important role in acrylamide formation in these synthetic potato models. Furthermore, glutamine and sodium alginate might have an inhibitory effect on acrylamide formation. A significant impact of frying technique was also revealed. On the other hand, GC-FID analysis detected acrylamide in only these three models, (glucose-fructose, sucrose and asparagine-glucose/fructose/sucrose models > LOD 333.33 µg.kg−1).